Evaluation of commercial forensic DNA extraction kits for decontamination and extraction of DNA from biological samples contaminated with radionuclides. (September 2019) - Toole, Kaitlyn; Roffey, Paul; Young, Emma; Cho, Kaymann; Shaw, Timothy; Smith, Michael; Blagojevic, Ned
Abstract: In preparing to respond to security incidents involving radioactive material, States should consider how they might address the unique challenge of analysing forensic evidence contaminated with these materials. In the case of DNA evidence, previous research has suggested that commercial forensic DNA extraction kits may be able to remove radioactive contamination from biological samples. If viable, this would allow the extraction and decontamination of biological samples to be undertaken in a laboratory equipped to handle radioactive material, with the subsequent quantification and profiling of extracted DNA performed in a conventional forensics laboratory. In order to inform the development of an operational capability, this study sought to expand upon previous work to provide a more comprehensive quantitative assessment of the efficacy of commercial DNA extraction kits for the removal of radionuclide contamination from biological samples and the quality of the resultant DNA profiles. Three commercial DNA extraction kits were tested for their ability to remove contaminating radionuclides. Two of these kits proved more effective at removing radionuclide contamination and produced DNA extracts of higher quality. Under all conditions tested in this study, decontamination efficiency was sufficient to allow the release of samples to a forensic laboratory. However, consistent with a prudent approach to radiation safety it is recommended that all samples be screened by gamma spectrometry prior to their release to a forensic laboratory in order to verify decontamination.